1990
DOI: 10.1080/00365519009089170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anti-insulin antibodies and its relation to severe hypoglycaemia in insulin-treated diabetic patients

Abstract: The prevalence of anti-insulin antibodies (AIABs) and their association with clinical parameters, metabolic control and severe hypoglycaemia were investigated in a geographically defined population of insulin-treated diabetic patients. Eighty per cent of the patients (479) delivered venous blood samples and answered a questionnaire on severe hypoglycaemic problems during a 12-month period. Circulating AIABs were demonstrable in 78% of the patients, being more common among those with type 1 diabetes and in long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…IAs could prevent insulin from binding its receptor, possibly resulting in the deterioration of the physiological effects of insulin; thereafter, insulin is released from the complexes irrespective of blood glucose concentrations, thus inducing hypoglycemia ( 14 18 ). However, the relationship between IAs and hypoglycemia was not determined in previous large-scale studies ( 13 , 19 , 20 ). One of the most important reasons for discrepancy among these findings may be the uncertainty of collecting information related to mild hypoglycemia based on subjects’ retrospective memory.…”
Section: Discussionmentioning
confidence: 91%
“…IAs could prevent insulin from binding its receptor, possibly resulting in the deterioration of the physiological effects of insulin; thereafter, insulin is released from the complexes irrespective of blood glucose concentrations, thus inducing hypoglycemia ( 14 18 ). However, the relationship between IAs and hypoglycemia was not determined in previous large-scale studies ( 13 , 19 , 20 ). One of the most important reasons for discrepancy among these findings may be the uncertainty of collecting information related to mild hypoglycemia based on subjects’ retrospective memory.…”
Section: Discussionmentioning
confidence: 91%
“…Since the introduction of purified insulins and human insulin, the prevalence of anti-insulin autoantibodies in patients previously treated with insulin has declined; however, prevalence remains high. Wredling et al found that among individuals with prior insulin treatment, up to 78% had insulin autoantibodies, particularly prevalent in type 1 DM patients and those with prolonged insulin use ( 21 ). Although rarely clinically significant, anti-insulin IgG autoantibodies can bind to exogenous insulin and form ICs that can deposit in various tissues, triggering the classical complement pathway and causing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies had the characteristics of low capacity and high affinity, which seldom cause hypoglycemia or hyperglycemia (5). From the literature, incidence of 0.16% of exogenous insulin-induced insulin antibodies in patients with diabetes had been reported (6).…”
Section: Discussionmentioning
confidence: 99%